AN ANALYSIS DIGITALTEXTBOOK FOR 2ND GRADE STUDENTS “MY NEXT WORDS” - Indah Yusmulya Putri; Evi Karlina Ambarwati (STKIP PGRI Jombang, 2023)
This study aims to analyze books with quality assessment and content analysis, this study describes the use of digital textbooks in managed learning for Grade 2 Elementary School students, this type of research method is used to discuss the use of textbooks used forincrease student learning motivation at the elementary school level. The book analyzed is a book published by the author EYLC team with the book title